Peripheral blood biomarkers as differential diagnostic markers of disease severity in neonates with hyperbilirubinemia - Dereje Mengesha Berta; Negesse Cherie; Berhanu Woldu; Aregawi Yalew; Elias Chane; Amare Mekuaninnit; Mebratu Tamir; Zufan Yiheyis; Abiy Ayele Angelo; Zewudu Mulatie; Adamu Kassie; Bisrat Birke Teketelew (Heliyon)
Background: Blood biomarkers offers an independent insight for the pathophysiology of hyperbilirubinemia. However, they are not practically used for the differential diagnosis of the hyperbilirubinemia severity. Therefore, the current study aimed to assess the differential diagnostic value of peripheral blood biomarkers with disease severity as an alternative. Methods: A cross-sectional study was done on conveniently selected neonates admitted with hyperbilirubinemia during study period. A 4 ml of venous blood was collected for laboratory analysis. The Sysmex KX-21 cellular analysis and Mindray BS-240 automated chemistry analyzer was used for complete blood count and biochemical analysis, respectively. The data were entered into Epi-data (4.6.0) and analyzed by STATA (14) software. The summary statistics were used. The Kruskal Wallis H tests were utilized to compare median differences between groups. To ascertain the diagnostic value, receiver operator characteristic (ROC) curve analysis was performed. Blood biomarkers score area under curve >.7 was selected as the best discriminative marker. The accepted threshold for statistical significance was set at P < 0.05. Result: Current study found that red blood cell (RBC) and absolute lymphocyte count (ALC) can differentiate high-risk from low and intermediate-risk groups. Similarly, they can also stratify low-risk group from the intermediate and high-risk groups. Besides, mean cell volume (MCV), absolute neutrophil count (ANC), neutrophil to lymphocyte (NLR) and platelet to lymphocyte ratio (PLR), can exhibit significant discriminative ability to differentiate high-risk groups from intermediate and low-risk groups as well as low-risk groups from intermediate and high-risk groups. Furthermore, for hemolytic type of hyperbilirubinemia, RBC, Hb (hemoglobin), ALC, NLR, and PLR were found as good diagnostic markers to differentiate high risk group for others. Whereas, for non-hemolytic type of hyperbilirubinemia, MCV, ALC, MPV (mean platelet volume) and NLR were found as good discriminative marker of high-risk group form others. Conclusions: Peripheral blood biomarkers were found as acceptable to good early differential diagnostic marker with significant association to disease severity. Thus, assessing of baseline blood biomarkers can help to differentiate disease severity in neonates with hyperbilirubinemia.